Some properties of purified and non-purified rumen tissue arginase in cattle - Erisir, M; Ozan, ST (Scientific Technical Research Council Turkey, 1999)
Some biochemical properties of purified and non-purified rumen tissue arginase were compared. Homogenization, heating, treatment with aceton, precipitation with ammonium sulfate, dialysis, several centrifugations, gel filtration on sephadex G-200 processes were utilized in the purification procedure of the enzyme. It was found that pre-incubation temperature (60 degrees C) of arginase and Km (4mM) to its substrate, L-arginine, did not change before and after purification. While pre-incubation period was 10 min and optimal pH 9.7 before purification, pre-incubation period was found to be 5 min and optimal pH 10 after purification. Purified enzyme achieved its highest activity at 2 mM MnCl2 concentration, whereas non-purified enzyme gave the highest activity at 1 mM MnCl2 concentration. Consequently, it was determined that Mn++ cations and preincubation were essential for the activation of the enzyme.
Si?ir Rumen Doku Arginazinin Saflaştirilmasindan Önce ve Saflaştirilmasindan Sonra Bazi Özellikleri
Keywords: cattle rumen tissue; arginase; purification; kinetic properties